Attitudes of university students towards First Aid and CPR. Pilot study with online questionnaires measuring training and performing First Aid and CPR - Katona, Zsolt (Arena-Journal of Physical Activities, 2019)
According to the Hungarian National Core Curriculum (NAT 2012) learning about First Aid is compulsory in primary school but cardiopulmonary resuscitation (CPR) is neglected. Pupils first learn about accident prevention and emergencies, and later (at the age of 12-15) a bit more about emergency situations and first aid embedded in biology and natural science subjects. The Hungarian populationâ€™s accident assistance is very low. In case of road accidents it is only 10% and the results are even worse for resuscitation, in spite of the fact that a successful exam in first aid and CPR is required for obtaining a driving license. How can this situation improve? Is it about the lack of knowledge or there are problems with attitude? Teachers have a huge responsibility for shaping both. Purpose: The present pilot study investigated the CPR knowledge and First Aid attitudes of university students (60 female and 41 male, mean age is 21,98 years) studying different majors like physical education, teacher training, coaching, recreation and sports. The main purpose of this research was to find out how the future teachers think about the first aid and resuscitation as a should be taught subject and what knowledge they have in this topic. Methods: The CPR attitude online questionnaire contained 12 items and answers on a 1-5 Likert scale indicated the studentsâ€™ predicted willingness toÂ help in sudden death situations (cronbach Î±:0,85). The second 15 items questionnaire using a 1-5 Likert scale also, provided statements about the importance of First Aid and CPR studies in primary education (cronbach Î±:0,74). There were also additional questions concerning studentsâ€™ socio-economic backgrounds physical self esteem and sporting habits. Results: By calculation Pearson Correlation and linear regression with SPSS 22.0 program, significant correlation was found between sporting habits during primary school and first-aid readiness/willingness (p= 0,05). Compared to male students, females tended to be more hesitant in a sudden death situation concerning a homeless man, due to fear of infection and prejudice. Former school studies in First Aid and CPR affected the willingness to help positively and both genders thought, that CPR should be taught in primary school already. Conclusions: So primary school training in first aid and CPR can be a defining part of a strategy for increasing bystander resuscitation rates and quality. Starting first aid education at early school age cuold be a successful method for training young people and change the attitude of the society